2021
DOI: 10.1039/d1sc04286f
|View full text |Cite
|
Sign up to set email alerts
|

Functional and protective hole hopping in metalloenzymes

Abstract: Hole hopping through tryptophan and tyrosine residues in metalloenzymes facilitates catalysis and prolongs survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 137 publications
0
65
0
Order By: Relevance
“…[1][2][3] The reason for conductivity is sought in chains of aromatic residues that can be oxidized and serve as relay elements to direct oxidizing electron holes to the protein surface to avoid oxidative damage of active sites of enzymes. [4][5][6] Each hop in this sequence is viewed as a single electron-transfer step 7 as traditionally described by the Marcus theory of electron transfer reactions. 8 This article reports molecular dynamics (MD) simulations and theoretical modeling of a single step in such a relay involving electron transfer between the active site of azurin protein (Figure 1, PDB 1AZU) and the nearby tryptophan residue as studied experimentally by Shih et al 4 Trp Cu R e ≃ 9.2 − 10.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The reason for conductivity is sought in chains of aromatic residues that can be oxidized and serve as relay elements to direct oxidizing electron holes to the protein surface to avoid oxidative damage of active sites of enzymes. [4][5][6] Each hop in this sequence is viewed as a single electron-transfer step 7 as traditionally described by the Marcus theory of electron transfer reactions. 8 This article reports molecular dynamics (MD) simulations and theoretical modeling of a single step in such a relay involving electron transfer between the active site of azurin protein (Figure 1, PDB 1AZU) and the nearby tryptophan residue as studied experimentally by Shih et al 4 Trp Cu R e ≃ 9.2 − 10.…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear that other strategies, such as addition of excess reducing agents taken to 'extinguish' histidyl radicals generated during the turnover of oxygenases, may offer themselves as means of increasing e ciency by prolonging the life of the catalyst 36 , be it an enzyme or-for that matter-a small molecule mimic. Our studies reported herein on LPMOs can therefore direct future research efforts on maximizing the e ciency of oxidative catalysts 13 .…”
Section: Discussionmentioning
confidence: 85%
“…In addition to these theoretical studies, evidence that LPMOs do indeed employ a high-valent copper species comes from experimental studies in which the enzyme has been 'shunted' with hydrogen peroxide (H 2 O 2 ) to perform the same selective oxidative chemistry on saccharidic substrates as with O 2 (analogous to 'shunt' studies on P450 enzymes) 12 . As with all oxygenase and peroxygenase enzymes, however, these intermediates cause damage to the enzyme through oxidative cleavage of bonds on adjacent amino acids 13 , an action which compromises signi cantly the e ciency of the enzyme 14 − 16 . An outstanding question about the mode of action of LPMOs is, therefore, what is the nature of this damage, and how does the enzyme mitigate/prevent it?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes a phenylalanine (Phe176) axial to the active site and a universally conserved alanine (Ala102) (Figure 3C) Forsberg, Røhr et al, 2014) that is believed to restrict coordination of cosubstrates in the solvent-exposed axial position and increase the likelihood an oxygen cosubstrate coordinated at the equatorial position will be activated for catalysis, thus conferring C1/C4 oxidizing specificity (Forsberg, Mackenzie et al, 2014;Borisova et al, 2015). A well conserved tryptophan (Trp167) among LPMOAA10s (Forsberg, Røhr et al, 2014;Meier et al, 2018) thought to protect the active site against oxidative inactivation during uncoupled turnovers (Loose et al, 2018;Paradisi et al, 2019;Gray & Winkler, 2021) is also present (Figures 3B,C).…”
Section: Copper-binding Active Site Primary Coordination Spherementioning
confidence: 99%